2009
DOI: 10.1681/asn.2008050454
|View full text |Cite
|
Sign up to set email alerts
|

Probability, Predictors, and Prognosis of Posttransplantation Glomerulonephritis

Abstract: Glomerulonephritis (GN) is the leading cause of chronic kidney disease among recipients of renal transplants. Because modern immunosuppressive regimens have reduced the incidence of rejection-related graft loss, the probability and clinical significance of posttransplantation GN (PTGN) requires reevaluation. In this Canadian epidemiologic study, we monitored 2026 sequential renal transplant recipients whose original renal disease resulted from biopsy-proven GN (36%), from presumed GN (7.8%), or from disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 51 publications
(56 reference statements)
10
59
3
1
Order By: Relevance
“…Some reports have suggested that primary EBV or CMV infection (excluded in our case) may trigger the recurrence of MPGN [11,12]. De novo occurrence of post-transplant MPGN type 1 is rare [10].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Some reports have suggested that primary EBV or CMV infection (excluded in our case) may trigger the recurrence of MPGN [11,12]. De novo occurrence of post-transplant MPGN type 1 is rare [10].…”
Section: Discussionmentioning
confidence: 61%
“…Family clustering suggests genetic susceptibility, including complement deficiencies [6][7][8][9]. Recurrence of MPGN after renal transplantation is common in pediatric patients [5,10]. The rate in children has been reported to be 30-77% with graft failure to recurrence in 17-50%.…”
Section: Discussionmentioning
confidence: 99%
“…FSGS was the leading form of de novo glomerular disease in a Canadian review (1). Although recurrent FSGS usually presents early post-transplant as a nephrotic syndrome, de novo FSGS is often detected more than 12 months after transplantation and associated with variable amounts of proteinuria (including nephrotic syndrome), hypertension, and progressive deterioration of renal allograft function.…”
Section: Fsgsmentioning
confidence: 99%
“…Post-transplant GN occurred in 24.3% of allografted patients whose original renal disease resulted from biopsy-proven GN compared with 10.5% of those patients with other types of renal or systemic diseases. Patients who developed glomerular diseases had significantly reduced graft survival (1). Post-transplant glomerular disease is generally divided into recurrences of the same original disease that affected the native kidney of the recipient and de novo disease, in which the post-transplant disease is unrelated to the original disease.…”
Section: Introductionmentioning
confidence: 99%
“…Post-transplant glomerular diseases influence graft function and impair the long-term graft survival (1). This disease is generally divided into two types, recurrent and de novo.…”
Section: Introductionmentioning
confidence: 99%